Effect of androgen suppression on bone mineral density in patients with prostate cancer - Chernichenko, O.A.; Sakalo, V.S.; Yakovlev, P.G.; Sakalo, A.V.; Zhylchuk, Y.V.; Zsolt, A. (Experimental Oncology, 2014)
The androgen-suppressive therapy (AST) in patients with prostate cancer (PC) may dramatically affect the bone mineral density (BMD), which puts patients at risk of severe adverse effects, such as weight-bearing bone fractures. Aim: To study the effect of AST on BMD in patients with non-metastatic hormone-sensitive PC treated with intermittent hormonal therapy, and effect of different total testosterone level on BMD. Materials and Methods: From 2011 to 2013 we treated 56 patients with non-metastatic hormone-naïve PC. Intermittent hormonal treatment with flutamide at a dose of 250 mg 3 times per day with nine monthly injections of luteinizing gonadotropic releasing hormone (LGnRH) [“treatment” period] followed by period of observance (“no treatment”) was administered. We evaluated the BMD of lumbar spine and both proximal thighs by means of dual-energy x-ray densitometry at the end of “treatment” period and at the end of “no treatment” period. Results: During the first treatment period, 44 of 56 patients (78.6%) experienced the reduction in BMD in both lumbar spine and thighs. Total testosterone level in all patients dropped to castration level. During the first period of “no treatment” there was an increase in BMD (p < 0.05) in 30 (68.2%) of 44 patients. The median time to recovery of total testosterone level to the level > 50 ng/dl was 91 days (from 30 to 308 days), and > 100 ng/dl was 110 days (from 49 to 343 days). The changes in BMD positively correlated with the changes in total testosterone level (correlation 0.18 [95% CI, 0.04–0.27], p = 0.009). The decline in total testosterone level in serum was followed by the decline in BMD value in the studied areas, and vice versa. Conclusions: The changes in BMD positively correlated with changes in total testosterone level. The BMD decreases during the androgen suppression and increases during the pause in the treatment. This demonstrates the benefit of intermittent AST in preventing osteoporosis, pathological bone fractures and possibly, bone metastases. Key Words: prostate cancer, hormone therapy, osteoporosis, bone mineral density.